Commercial contract law : transatlantic perspectives - DiMatteo, Larry A. (Cambridge : Cambridge University Press, 2013)
'This book focuses on the law of commercial contracts as constructed by the U.S. and UK legal systems. Leading scholars from both sides of the Atlantic provide works of original scholarship focusing on current debates and trends from the two dominant common law systems. The chapters approach the subject areas from a variety of perspectives - doctrinal analysis, law and economic analysis, and social-legal studies, as well as other theoretical perspectives. The book covers the major themes that underlie the key debates relating to commercial contract law: role of consent; normative theories of contract law; contract design and good faith; implied terms and interpretation; policing contract behavior; misrepresentation, breach, and remedies; and the regional and international harmonization of contract law. Contributors provide insights on the many commonalities, but more interestingly, on the key divergences of the United States and United Kingdom's approaches to numerous areas of contract law. Such a comparative analysis provides a basis for future developments and improvements of commercial contract law in both countries, as well as other countries that are members of the common law systems. At the same time, insights gathered here should also be of interest to scholars and practitioners of the civil law tradition'--
Machine generated contents note: Part I. The Role of Consent: 1. Transatlantic perspectives: fundamental themes and debates Larry A. DiMatteo, Qi Zhou and Se;verine Saintier; 2. Competing theories of contract: an emerging consensus? Martin A. Hogg; 3. Contracts, courts and the construction of consent Tom W. Joo; 4. Are mortgage contracts promises? Curtis Bridgeman; Part II. Normative Views of Contract: 5. Naturalistic contract Peter A. Alces; 6. Contract in a networked world Roger Brownsword; 7. Contract, transactions, and equity T. T. Arvind; Part III. Contract Design and Good Faith: 8. Reasonability in contract design Nancy S. Kim; 9. Managing change in uncertain times: relational view of good faith Zoe Ollerenshaw; Part IV. Implied Terms and Interpretation: 10. Implied terms in English contract law Richard Austen-Baker; 11. Contract interpretation: judicial rule, not party choice Juliet Kostritsky; Part V. Policing Contracting Behavior: 12. The paradox of the French method of calculating the compensation of commercial agents and the importance of conceptualising the remedial scheme under Directive 86/653 Severine Saintier; 13. Unconscionability in American contract law Chuck Knapp; 14. Unfair terms in comparative perspective: software contracts Jean Braucher; 15. (D)CFR initiative and consumer unfair terms Mel Kenny; Part VI. Misrepresentation, Breach and Remedies: 16. Remedies for misrepresentation: an integrated system David Capper; 17. Re-examining damages for fraudulent misrepresentation James Devenney; 18. Remedies for documentary breaches: English law and the CISG Djakhongir Saidov; Part VII. Harmonizing Contract Law: 19. Harmonisation European contract law: default and mandatory rules Qi Zhou; 20. Harmonization and its discontents: a critique of the transaction cost argument for a European contract law David Campbell and Roger Halson; 21. Europeanisation of contract law and the proposed common European sales law Hector MacQueen; 22. Harmonization of international sales law Larry A. DiMatteo.
Includes bibliographical references and index.
Keywords: Contracts -- United States; Contracts -- United Kingdom; Commercial law -- United States; Commercial law -- United Kingdom; Common law -- United States; Common law -- United Kingdom